Taou, its paths into the Bible (I): Revisiting the Inception of the Taou-Logos Translation in Protestant Chinese Bible - ZHOU, Elsie Ge-Shan (Journal of Research for Christianity in China (JRCC), 2024)
This article contributes to an extensive research initiative aimed at investigating the early reception history of the Taou-Logos rendering within the prologue of the Johannine Gospel, a seminal part of Chinese Bible translation history. The study endeavors to explore the historical context of this translation choice, an aspect hitherto overshadowed by the predominance of comparative conceptual analysis in scholarly discourse. While initially aligning with the prevailing view that posits the Taou-Logos translation’s formal inception within the second-generation Chinese Bible of 1836, the present inquiry extends its scope to include general missionary publications from the London Missionary Society that predate this edition. It uncovers earlier instances of the Taou-Logos translation in Robert Morrison’s Domestic Instructor (1832) and Walter H. Medhurst’s the Harmony of the Gospels (1834), thereby challenging the accepted timeline and offering specific nodes that may facilitate a more profound contextual examination.